Pengaruh good corporate governance, profitabilitas, dan ukuran perusahaan terhadap pengungkapan tanggung jawab sosial perushaan pada perusahaan real estate dan property yang terdaftar di bursa efek indonesia (2010-2011) - Oi Sanjaya; Taufeni Taufik; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this experiment is knowing the influence of good corporate governance, profitability and company measurement to company social responsibility.The population of this experiment is all of the company that is registered on BEI in 2010-2011. The taken samples are 54 company during two years. The used data is secondary data with collecting data method by downloading on web BEI and literature. Analisys data method that is used on this experiment is multiple regression with helping of software SPSS 17.0 version.The experiment result shows that institusional ownership has the effect on CSR with t-count 3.354, t-table 2.012 , significancy 0.002. The profability has the effect on CSR with t-count 2.843, t-table 2.012, significancy 0.007. The company measurement has the effect on CSR with t-count 3.333,t-table 2.012, significancy 0.002. Independent Comissioners has no effect on CSR with t-count -1.811, t-table 2.012, and significancy 0.076. Managerial ownership has no effect on CSR with t-count -1.256, t-table 2.012, significancy 0.215. Audit comittee has no effect on CSR with t-count1.797, t-table 2.02, significancy 0.079. Adjusted score R square is 0.597 means 59.7% independent variable on this experiment be able to give an effect on dependent Variable, and the left 40.3% is explained by otehr variable that’s not entered on this experiment, like foreighn ownership, Board of Commissioners, Leverage, Liquidity, company ages, company profile.Keywords: Institutional Ownership, Independent Board of Commissioners, Managerial Ownership, Audit Committee, profitability, firm size, CSR